"O" No: A Reddit Analysis of Orgasmic Dysfunction. (1st August 2022) - Belcher, R; Sim, D; Meykler, M; Owens-Walton, J; Hassan, N; Rubin, R; Malik, R
ABSTRACT: Introduction: Orgasmic dysfunction includes reduced orgasmic intensity, decreased orgasm frequency and inability to achieve orgasm. Issues with orgasming are often multi-factorial in origin and can cause significant distress to patients. Objective: We aimed to evaluate the experience of women with orgasmic dysfunction on Reddit, an anonymous forum-based platform that allows users to interact with a global audience. Methods: The subreddit "TwoXChromosomes" was queried using the Reddit Application Programming Interface (API) for posts using the keywords "orgasm" and "climax". Posts that were deleted, archived or unrelated to themes of orgasm were excluded. Threads were qualitatively analyzed using the grounded theory approach. Five independent researchers read and coded each thread identifying dominant themes and emergent concepts. Results: Qualitative analysis of 108 threads and approximately 6, 300 comments resulted in 5 major categories: psychological aspect of orgasms, difficulty orgasming with partners, partners' response to orgasmic dysfunction, types of orgasms, and treatments for orgasmic dysfunction. Preliminary themes included (1) the presence of an emotional component or history of trauma resulting in orgasmic difficulty, (2) difficulty orgasming with a partner regardless of ability to orgasm during masturbation, and mixed partner responses to orgasmic dysfunction, with approximately half of posters reporting a supportive sexual partner who was interested in their sexual satisfaction while the remainder of posters reported partner dissatisfaction. (3) variety of stimulation required to orgasm, (4) the definition of a "normal orgasm and (5) self-motivated treatment for orgasmic dysfunction, including clitoral stimulation devices and masturbation techniques, with few posters discussing their orgasmic dysfunction with health care providers. Conclusions: Overall, Reddit provides a medium for individuals with orgasmic dysfunction to discuss their experiences. Posts addressed users' inability to orgasm, the interplay with their mental health and relationships, types of stimulation and treatments. Interestingly, very few posts discussed seeking out medical care for orgasmic dysfunction, potentially suggesting that women do not classify their orgasmic dysfunction as a health issue. The obvious prevalence of orgasmic dysfunction with little discussion surrounding healthcare reveals a large gap in sexual health counseling, indicating the need for expanded sexual health screening and detailed clinician-patient counseling. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Sprout (Raliegh, NC), Absorption Pharmaceuticals, Urovant Sciences, Inc.